Farm-level sustainability assessment in Mediterranean environments: Enhancing decision-making to improve business sustainability - Iakovidis, Dimitrios; Gadanakis, Yiorgos; Park, Julian (My University, 2022)
In typical Mediterranean settings farming systems are key components and have an impact on the community structure and the environment in which they take place hence it is important to develop tools for Sustainability Assessment (SA). To enable positive change it is necessary to effectively allocate resources. Thus, it is important to understand how farmers’ decision-making impacts their farm's sustainability performance and their awareness and use of Decision Support Tools (DST) for sustainable management. Twenty representative farms were selected from the National Farm Accountancy Data Network (FADN) for the regional unit of Argolida (Peloponnese, Greece). To investigate sustainability on these farms an indicator-based method, RISE 3.0, was employed to evaluate the current situation and semi-structured phone interviews were used to identify and analyse patterns and attitudes within the data regarding decision-making, sustainability performance and DST with the help of thematic analysis. The results demonstrate that the decision-making process was poorly informed and not always evidence-based while the concept of sustainability was not well understood by most of the farmers. The sustainability assessment illustrated the specific strengths and weaknesses of farm businesses in the area whereas the correlation of the RISE assessment with perceptions of farmers on decision-making and sustainability performance identified the challenges of moving towards more sustainable systems in typical Mediterranean environments.
Keywords: Farm management; Sustainability Assessment; Decision-making; RISE; Northern Meditterranean